Discrimination among thermophilic Campylobacter species by polymerase chain reaction amplification of 23S rRNA gene fragments. - Eyers, M (1993)
By comparing nucleic acid sequences determined for one of the most variable areas of 23S rRNA genes of 23 Campylobacter strains, we were able to identify regions specific for thermophilic Campylobacter strains. Oligonucleotide primers corresponding to these unique regions were synthesized and used in the polymerase chain reaction. One primer pair selectively detected all thermophilic Campylobacter species, while four other primer pairs allowed discrimination among the thermophilic species Campylobacter coli, Campylobacter jejuni subsp. jejuni, Campylobacter lari, and Campylobacter upsaliensis. All primer sets were tested successfully on a large number of clinical isolates.